2019
DOI: 10.1002/nop2.247
|View full text |Cite
|
Sign up to set email alerts
|

Young adult patients’ experience of living with mechanical circulatory support: A phenomenological hermeneutical study

Abstract: Aim To describe young adult patients’ experiences of living with a mechanical circulatory support (MSC) as a bridge to heart transplantation and impact of self‐efficacy. Design A qualitative and explorative interview study. Methods Eight interviews with adult participants were conducted and analysed using the phenomenological hermeneutical method. Results An overall theme, “Navigating from helplessness to feeling s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…According to a patient on MCS, feelings of powerlessness stemmed from being "hooked up to a machine that kept you alive" and having to place full trust in health care professionals. 18 Due to the invasive nature and critical illness surrounding MCS, psychiatric comorbidities such as depression or anxiety are not uncommon in MCS patients. 19 One patient described having panic attacks over seeing tubes connected to their body and being constantly aware of the presence of the pump "invading" their body.…”
Section: Patient Impacts Of Mcsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to a patient on MCS, feelings of powerlessness stemmed from being "hooked up to a machine that kept you alive" and having to place full trust in health care professionals. 18 Due to the invasive nature and critical illness surrounding MCS, psychiatric comorbidities such as depression or anxiety are not uncommon in MCS patients. 19 One patient described having panic attacks over seeing tubes connected to their body and being constantly aware of the presence of the pump "invading" their body.…”
Section: Patient Impacts Of Mcsmentioning
confidence: 99%
“…Studying the subjective experience of MCS is important to understand patient decision-making and act ethically under the principle of nonmaleficence. Through interviewing patients who had experienced living with MCS, common themes have emerged: feelings of helplessness, loneliness, decreased self-efficacy, and newfound inner strength in enduring MCS 18. Fortunately, despite these negative feelings, many LVAD patients agreed that they would make the same choice if they had to do it over again 8…”
Section: Patient Impacts Of Mcsmentioning
confidence: 99%
“…Being an adult MCS-recipient means a liminal existence [ 2 ] and vocational adjustment [ 3 ]. Young adult patients receiving MCS navigate from helplessness to feeling strong in their new reality [ 4 ]. Some patients receiving MSC might prefer to continue it even when transplant becomes an option [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…5 Following implantation, patients experienced their body as different, were disgusted by their own body, felt ashamed by their changed appearance, and felt that their body had been invaded. 6 On discharge from the hospital, along with the positive outcomes of the LVAD support, patients reported feelings of awe and dismay when looking at themselves in the mirror. 7 Almost half (47%) the patients felt that the LVAD negatively affected their selfimage, which more than half thought was important for sexual satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…11 Among young adults living with mechanical circulatory support, feeling trust and confidence in the ventricular assist device and seeing it as a friend were among the main themes identified. 6 A systematic review by Adams et al (2015) reported on LVAD ability to improve patients' quality of life. 12 Among LVAD supported patients with totally implantable or extracorporeal LVAD, quality of life scores were highest among the totally implantable group.…”
Section: Introductionmentioning
confidence: 99%